A Very Simple and Sensitive Spectrofluorimetric Method Based on the Oxidation with Cerium (IV) for the Determination of Four Different Drugs in Their Pharmaceutical Formulations - Ahad Bavili-Tabrizi, Farshad Bahrami, Hossein Badrouj (Tabriz University of Medical Sciences, 2017)
Background: Methyldopa is a catecholamine widely used as an antihypertensive agent. Pioglitazone is an oral anti-hyperglycemic agent. It is used for the treatment of diabetes mellitus type 2. A survey of the literature reveals that only one spectrofluorimetric method has been reported for the determination of pioglitazone in pharmaceutical preparations. Atenolol and metoprolol are prescription drugs of the β-blocker class with hypotensive action to treat angina, MI, alcohol syndrome, hypertension, and arrhythmias. A survey of the literature reveals that several spectrofluorimetric methods have been reported for the determination of atenolol and metoprolol in pharmaceutical preparations. In continuing of our studies on the developing of simple and fast spectrofluorimetric methods for determination of drugs and active ingredients, in this work we have developed a spectrofluorimetric method based on the oxidation with cerium (IV) for the determination of studied drugs in their pharmaceutical formulations. Methods: A simple, rapid and sensitive spectrofluorimetric method was developed for the determination of studied drugs in pharmaceutical formulations. Proposed method is based on the oxidation of these drugs with Ce (IV) to produce Ce (III), and its fluorescence was monitored at 356 ± 3 nm after excitation at 254 ± 3 nm. Results: The variables affecting oxidation of each drug were studied and optimized. Under the experimental conditions used, the calibration graphs were linear over the range of 25-450, 50-550, 15-800 and 15-800 ng/mL in the case of atenolol, metoprolol, pioglitazone and methyldopa, respectively. The limit of detection was found to be 8.27, 16.5, 1.52 and 5.08 ng/mL in the case of atenolol, metoprolol, pioglitazone and methyldopa, respectively. Intra- and inter-day assay precisions, expressed as the relative standard deviation (RSD), were lower than 3% in all cases. Conclusion: The proposed method was applied to the determination of studied drugs in their pharmaceutical formulations by good recoveries in the range 92-113%.